توانستەكانی گەشەپێدانی پیشەسازی دەرهێنانی نەوت لە ناوچە كوردستانیەكانی دەرەوەی بەڕێوەبردنی هەرێم (توێژینەوەی هەڵێنجراو) - نەقشبەندی, ئازاد محمد امین كاكە شێخ; حسن, هاشم بهجت (Sulaimani Journal for Humanities, 2023)
Potentials of developing the oil extraction industry in the Kurdistan areas outside the administration of the region The study aims to determine the potentials of developing the oil extraction industry in the Kurdistan areas outside the administration of the region. The importance of the study comes from its contribution to assessing the current reality of the oil extraction industry in the study area and its future prospects. To achieve the aim of the study, and due to the nature of its subject, it was found appropriate to classify it as follows: The first axis: the natural potentials for the development of the oil extraction industry in the Kurdistan areas outside the administration of the region. The second axis: the human potentials for the development of the oil extraction industry in the Kurdistan areas outside the administration of the region. The study concluded with the most prominent conclusions and some recommendations.
Keywords: potentials; development; oil extraction; Kurdistan areas